PENERAPAN MANAJEMEN STRATEGI DALAM MENINGKATKAN JUMLAH MAHASISWA FAKULTAS TEKNIK DI UNIVERSITAS XYZ (Teknik Industri Unikom, 2023)
The existence of students plays a key role in supporting higher education institutions. Improvement of higher education institutions needs to be carried out to influence the decisions of prospective students about continuing their studies. The importance of proper strategic management in attracting prospective students to study at XYZ University's Faculty of Engineering. The condition of XYZ University's Faculty of Engineering, which was only established in 2017, causes the number of students to fluctuate year after year. This research was conducted to provide solutions for determining the best management strategy for increasing the number of prospective students. The results of multiple linear regression measurements show that promotions, tuition fees, supporting facilities, service quality, and alumni networks have a significant effect on prospective students' decisions about continuing their studies. Through SWOT analysis, alternative strategies are produced that are divided into S-O strategy, W-O strategy, S-T strategy and W-T strategy.